THE INFLUENCE OF TIKTOK MARKETING, LIVE STREAMING, CONTENT MARKETING, AND INFLUENCER MARKETING ON PURCHASE DECISION AMONG GENERATION Z TIKTOK USERS: A COMPREHENSIVE LITERATURE REVIEW - Alifia Lisda; Verin Stefania (Journal of Global Business and Management Review, 2026)
The purpose of this study is to investigate how Generation Z TikTok users' purchasing decisions are impacted by TikTok marketing, live streaming, content marketing, and influencer marketing. Findings from pertinent national and international scholarly publications were synthesised utilising a qualitative approach and the Comprehensive Literature Review method. A thorough analysis of scholarly works on digital marketing and consumer behaviour in the TikTok ecosystem was used to gather data. The results show that by improving customer engagement, trust, information quality, and perceived credibility, TikTok marketing, live streaming, content marketing, and influencer marketing have a beneficial impact on purchase decisions. The research also emphasises how attentive Generation Z customers are to genuine and participatory digital marketing tactics. The study concludes that integrating these marketing approaches can effectively support consumer purchase decisions on TikTok.